Photocatalytic synergistic biofilms enhance tetracycline degradation and conversion - Chuanbao Xiao; Jilin Yuan; Linyang Li; Nianbing Zhong; Dengjie Zhong; Quanhua Xie; Haixing Chang; Yunlan Xu; Xuefeng He; Min Li (Environmental Science and Ecotechnology, 2023)
Tetracyclines are refractory pollutants that cause persistent harm to the environment and human health. Therefore, it is urgently necessary to develop methods to promote the efficient degradation and conversion of tetracyclines in wastewater. This report proposes a photobiocatalytic synergistic system involving the coupling of GeO2/Zn-doped phosphotungstic acid hydrate/TiO2 (GeO2/Zn-HPW/TiO2)-loaded photocatalytic optical hollow fibers (POHFs) and an algal–bacterial biofilm. The GeO2/Zn-HPW/TiO2 photocatalyst exhibits a broad absorption edge extending to 1000 nm, as well as high-efficiency photoelectric conversion and electron transfer, which allow the GeO2/Zn-HPW/TiO2-coated POHFs to provide high light intensity to promote biofilm growth. The resulting high photocatalytic activity rapidly and stably reduces the toxicity and increases the biodegradability of tetracycline-containing wastewater. The biofilm enriched with Salinarimonas, Coelastrella sp., and Rhizobium, maintains its activity for the rapid photocatalytic degradation and biotransformation of intermediates to generate the O2 required for photocatalysis. Overall, the synergistic photocatalytic biofilm system developed herein provides an effective and efficient approach for the rapid degradation and conversion of water containing high concentrations of tetracycline.